Graphene-modified high-flame-retardant SMC composite material and preparation method thereof
Patent Information
- Application Number
- CN202610543147.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-23
AI Technical Summary
但二维纳米材料直接添加,会由于相容性差、阻燃效率不高等缺点限制片状模塑料的应用
本发明制备的SMC复合材料是以不饱和聚酯树脂为主要树脂,再加入聚苯乙烯、引发剂、润湿分散剂、短切玻璃纤维、石墨烯杂化阻燃剂、脱模剂、碳酸钙和氧化镁制备而成,不仅具有复合材料优异的综合性能,还通过石墨烯杂化阻燃剂的引入赋予基体高阻燃性能。
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material technology, specifically to a graphene-modified high flame-retardant SMC composite material and its preparation method. Background Technology
[0002] Sheet molding compounds (SMCs), as high-performance fiber-reinforced composite materials, are widely used in transportation, electronics, construction, and other fields due to their excellent mechanical strength, dimensional stability, and design freedom. However, their commonly used unsaturated polyester resin matrices are highly flammable, posing a serious fire safety hazard, which greatly limits their application in scenarios with stringent fire protection requirements. Traditional solutions involve adding halogenated, phosphorus-based, nitrogen-based, or inorganic hydroxide flame retardants. While these flame retardants improve the flame retardant properties of the material to some extent, they often face multiple challenges, including high addition amounts, poor compatibility with the matrix, deterioration of the material's mechanical properties and processing flowability, and increasingly stringent environmental regulations (especially for halogenated flame retardants).
[0003] In recent years, the emergence of two-dimensional nanomaterials such as graphene has provided a novel approach to solving this problem. Graphene, with its unique layered structure, extremely high specific surface area, and excellent thermal stability, is considered ideal for constructing physical barrier layers, bringing revolutionary opportunities for high-performance flame-retardant modification. However, the direct addition of two-dimensional nanomaterials limits the application of sheet molding compounds due to poor compatibility and low flame-retardant efficiency. Therefore, developing a novel flame-retardant technology that is efficient, requires low additives, is environmentally friendly, and can balance the comprehensive performance of composite materials has become an urgent need for the development of SMC composite materials. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a graphene-modified high flame-retardant SMC composite material and its preparation method.
[0005] The objective of this invention can be achieved through the following technical solutions: A graphene-modified high flame-retardant SMC composite material comprises the following raw materials in parts by weight: 60-80 parts unsaturated polyester resin, 10-18 parts polystyrene, 8-15 parts graphene hybrid flame retardant, 2-4 parts initiator, 1-3 parts release agent, 45-55 parts calcium carbonate, 2.5-4.5 parts magnesium oxide, 3-6 parts wetting and dispersing agent, and 55-75 parts chopped glass fiber. Furthermore, the initiator is one of benzoyl peroxide or dicumyl peroxide; Furthermore, the release agent is zinc stearate; Furthermore, the wetting and dispersing agent is BYK-W996; The graphene hybrid flame retardant is prepared by the following steps: Step A1: Place a beaker containing concentrated sulfuric acid in an ice-water bath, add graphite powder and stir evenly, then add sodium nitrate and stir for 10 minutes, then add potassium permanganate in three portions and stir at room temperature for 12 hours to form a gel, then slowly add deionized water to dilute into a suspension, then add 30wt% hydrogen peroxide and stir for 24 hours, centrifuge, wash until neutral, freeze dry to obtain graphene oxide. Furthermore, in step A1, the ratio of concentrated sulfuric acid, graphite powder, sodium nitrate, potassium permanganate, deionized water, and hydrogen peroxide is 50mL:2g:0.5-1g:5-7g:300mL:20-30mL. Step A2: Under nitrogen atmosphere, add 2,5-furandicarboxylic acid, melamine, DMF (N,N-dimethylformamide) and 98wt% concentrated sulfuric acid to a flask in sequence, stir thoroughly, then heat to 120-140℃ and reflux for 7-9 hours. Add water and shake for 30 minutes, then let stand to separate the layers. Collect the organic layer, wash the organic layer, and dry it under vacuum to obtain the triazine-furan derivative. Furthermore, in step A2, the ratio of 2,5-furandicarboxylic acid, melamine, DMF, concentrated sulfuric acid, and water is 0.01-0.03 mol: 0.021-0.063 mol: 100 mL: 0.2-0.3 mL: 100 mL; Further, the washing of the organic layer in step A2 involves first washing three times with a 0.1 mol / L sodium bicarbonate solution, and then washing three times with water; Step A3: Disperse graphene oxide in water by ultrasonication for 30 min, adjust the pH of the system to 7.5-8.5, add triazine-furan derivative and sonicate while stirring for 15 min, then transfer to an oil bath at 60℃ and stir for 12 h. Centrifuge, wash and dry to obtain functionalized graphene. Furthermore, in step A3, the ratio of graphene oxide, water, and triazine-furan derivative is 1g:50mL:0.5-1.5g; Furthermore, the pH adjustment of the system described in step A3 is performed using a 0.5 mol / L sodium hydroxide solution; Step A4: Mix functionalized graphene in water and stir until uniform, then add phytic acid and ultrasonically disperse for 30 minutes, then stir at room temperature for 1-2 hours, remove the solvent by rotary evaporation, and vacuum dry to obtain graphene hybrid flame retardant. Furthermore, in step A4, the ratio of functionalized graphene, water, and phytic acid is 3g:50mL:2-4g.
[0006] A method for preparing a graphene-modified high flame-retardant SMC composite material includes the following steps: Step S1: Weigh the raw materials according to the weight parts, add unsaturated polyester resin, polystyrene, initiator and wetting and dispersing agent into the mixer and mix evenly, then add graphene hybrid flame retardant, release agent, calcium carbonate and magnesium oxide and mix evenly to obtain the mixed paste. Step S2: Spread chopped glass fibers evenly on one side of a polypropylene film, then coat the surface of the chopped glass fibers with a mixed paste, then use a pressure roller to fully impregnate the mixed paste and glass fibers, then wind them up with a winding machine, and then transfer them to an oven for curing to obtain graphene-modified high flame-retardant SMC composite material. Furthermore, the aging process temperature in step S2 is 50-80℃.
[0007] The beneficial effects of this invention are: The SMC composite material prepared by this invention is made by adding polystyrene, initiator, wetting and dispersing agent, short glass fiber, graphene hybrid flame retardant, release agent, calcium carbonate and magnesium oxide as the main resin. It not only has the excellent comprehensive performance of composite materials, but also imparts high flame retardant properties to the matrix through the introduction of graphene hybrid flame retardant.
[0008] The graphene hybrid flame retardant used in this invention differs from traditional single inorganic and organic flame retardants, offering advantages such as low dosage and high flame retardant efficiency. This graphene hybrid flame retardant utilizes the synergistic effect of graphene's physical barrier effect and the chemical flame retardant effect of the triazine-furan / phytic acid system to give the composite material high flame retardant performance. Specifically, the triazine ring in the triazine-furan structure decomposes upon heating to produce non-flammable gases such as NH3 and N2. These gases effectively dilute flammable gases and oxygen concentrations, thereby inhibiting the combustion chain reaction. Simultaneously, phytic acid contains a large amount of phosphorus, which transforms into PO· free radicals during combustion. These PO· free radicals can capture these free radicals (H· and HO· free radicals), converting them into more stable substances, thus "quenching" the flame. Furthermore, phytic acid, as a highly efficient phosphorus source, can promote the polymerization of the polymer matrix (such as...) upon heating. Saturated polyester resin undergoes dehydration, cross-linking, and cyclization reactions to form a denser carbon layer. Graphene sheets, as two-dimensional nanomaterials, act as a physical framework in the condensed phase. They are embedded in the carbon layer generated by phytic acid and triazine-furan catalysis, greatly enhancing the mechanical strength, density, and continuity of the carbon layer. Without graphene, the carbon layer formed may be loose and porous, easily dispersed by heat flow and flame. Furthermore, during combustion, graphene will rearrange on the surface of the material to form a continuous and dense "armor" or "barrier," thereby delaying the diffusion of heat into the material, preventing the leakage of internal combustible gases, isolating external oxygen from entering, and confining the smoke particles generated by polymer decomposition inside the material. Detailed Implementation
[0009] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0010] Example 1: Graphene hybrid flame retardant was prepared by the following steps: Step A1: Place a beaker containing 50 mL of concentrated sulfuric acid in an ice-water bath, add 2 g of graphite powder and stir evenly, then add 0.5 g of sodium nitrate and stir for 10 min, then add 5 g of potassium permanganate in three portions and stir at room temperature for 12 h to form a gel, then slowly add 300 mL of deionized water to dilute it into a suspension, then add 20 mL of 30 wt% hydrogen peroxide and stir for 24 h, centrifuge, wash until neutral, freeze dry to obtain graphene oxide; Step A2: Under nitrogen atmosphere, add 0.01 mol 2,5-furandicarboxylic acid, 0.021 mol melamine, 100 mL DMF, and 0.2 mL 98 wt% concentrated sulfuric acid sequentially to a flask, stir thoroughly, and then heat to 120 °C and reflux for 7 h. Then add 100 mL water and shake for 30 min, and let stand to separate the layers. Collect the organic layer, wash the organic layer, and vacuum dry to obtain the triazine-furan derivative. The organic layer is washed three times with 0.1 mol / L sodium bicarbonate solution and then three times with water. Step A3: Disperse 1g of graphene oxide in 50mL of water by ultrasonication for 30min, adjust the pH of the system to 7.5, add 0.5g of triazine-furan derivative and sonicate while stirring for 15min, then transfer to an oil bath at 60℃ and stir for 12h. Centrifuge, wash and dry to obtain functionalized graphene. The pH of the system is adjusted using 0.5mol / L sodium hydroxide solution. Step A4: Mix 3g of functionalized graphene in 50mL of water and stir until homogeneous. Then add 2g of phytic acid and ultrasonically disperse for 30min. Stir at room temperature for 1h, remove the solvent by rotary evaporation, and vacuum dry to obtain the graphene hybrid flame retardant.
[0011] Example 2: Graphene hybrid flame retardant was prepared by the following steps: Step A1: Place a beaker containing 50 mL of concentrated sulfuric acid in an ice-water bath, add 2 g of graphite powder and stir evenly, then add 0.75 g of sodium nitrate and stir for 10 min, then add 6 g of potassium permanganate in three portions and stir at room temperature for 12 h to form a gel, then slowly add 300 mL of deionized water to dilute it into a suspension, then add 25 mL of 30 wt% hydrogen peroxide and stir for 24 h, centrifuge, wash until neutral, freeze dry to obtain graphene oxide; Step A2: Under nitrogen atmosphere, add 0.02 mol 2,5-furandicarboxylic acid, 0.042 mol melamine, 100 mL DMF, and 0.25 mL 98 wt% concentrated sulfuric acid sequentially to a flask, stir thoroughly, and then heat to 130 °C and reflux for 8 h. Then add 100 mL water and shake for 30 min, and let stand to separate the layers. Collect the organic layer, wash the organic layer, and vacuum dry to obtain the triazine-furan derivative. The organic layer is washed three times with 0.1 mol / L sodium bicarbonate solution and then three times with water. Step A3: Disperse 1g of graphene oxide in 50mL of water by ultrasonication for 30min, adjust the pH of the system to 8, add 1g of triazine-furan derivative and sonicate while stirring for 15min, then transfer to an oil bath at 60℃ and stir for 12h. Centrifuge, wash and dry to obtain functionalized graphene. The pH of the system is adjusted by using 0.5mol / L sodium hydroxide solution. Step A4: Mix 3g of functionalized graphene in 50mL of water and stir until homogeneous. Then add 3g of phytic acid and ultrasonically disperse for 30min. Stir at room temperature for 1.5h, remove the solvent by rotary evaporation, and vacuum dry to obtain the graphene hybrid flame retardant.
[0012] Example 3: Graphene hybrid flame retardant was prepared by the following steps: Step A1: Place a beaker containing 50 mL of concentrated sulfuric acid in an ice-water bath, add 2 g of graphite powder and stir evenly, then add 1 g of sodium nitrate and stir for 10 min, then add 7 g of potassium permanganate in three portions and stir at room temperature for 12 h to form a gel, then slowly add 300 mL of deionized water to dilute it into a suspension, then add 30 mL of 30 wt% hydrogen peroxide and stir for 24 h, centrifuge, wash until neutral, freeze dry to obtain graphene oxide; Step A2: Under nitrogen atmosphere, add 0.03 mol 2,5-furandicarboxylic acid, 0.063 mol melamine, 100 mL DMF, and 0.3 mL 98 wt% concentrated sulfuric acid sequentially to a flask, stir thoroughly, and then heat to 140 °C and reflux for 9 h. Then add 100 mL water and shake for 30 min, and let stand to separate the layers. Collect the organic layer, wash the organic layer, and vacuum dry to obtain the triazine-furan derivative. The washing of the organic layer is done by washing three times with 0.1 mol / L sodium bicarbonate solution and then washing three times with water. Step A3: Disperse 1g of graphene oxide in 50mL of water by ultrasonication for 30min, adjust the pH of the system to 8.5, add 1.5g of triazine-furan derivative and sonicate while stirring for 15min, then transfer to an oil bath at 60℃ and stir for 12h. Centrifuge, wash and dry to obtain functionalized graphene. The pH of the system is adjusted using 0.5mol / L sodium hydroxide solution. Step A4: Mix 3g of functionalized graphene in 50mL of water and stir until homogeneous. Then add 4g of phytic acid and ultrasonically disperse for 30min. Stir at room temperature for 2h, remove the solvent by rotary evaporation, and vacuum dry to obtain the graphene hybrid flame retardant.
[0013] Example 4: A method for preparing a graphene-modified high flame-retardant SMC composite material includes the following steps: 60 parts unsaturated polyester resin, 10 parts polystyrene, 8 parts graphene hybrid flame retardant prepared in Example 1, 2 parts benzoyl peroxide or dicumyl peroxide, 1 part zinc stearate, 45 parts calcium carbonate, 2.5 parts magnesium oxide, 3 parts wetting and dispersing agent BYK-W996, and 55 parts chopped glass fiber. Step S1: Weigh the raw materials according to the weight parts, add unsaturated polyester resin, polystyrene, benzoyl peroxide and wetting and dispersing agent BYK-W996 into a mixer and mix evenly, then add the graphene hybrid flame retardant prepared in Example 1, zinc stearate, calcium carbonate and magnesium oxide and mix evenly to obtain a mixed paste. Step S2: Spread chopped glass fibers evenly on one side of a polypropylene film, then coat the surface of the chopped glass fibers with a mixed paste, then use a pressure roller to fully impregnate the mixed paste and glass fibers, then wind them up with a winding machine, and then transfer them to an oven for curing to obtain graphene-modified high flame-retardant SMC composite material. The curing temperature is 50℃.
[0014] Example 5: A method for preparing a graphene-modified high flame-retardant SMC composite material includes the following steps: 70 parts unsaturated polyester resin, 14 parts polystyrene, 12 parts graphene hybrid flame retardant prepared in Example 2, 3 parts dicumyl peroxide, 2 parts zinc stearate, 55 parts calcium carbonate, 3.5 parts magnesium oxide, 4.5 parts wetting and dispersing agent BYK-W996, and 65 parts chopped glass fiber. Step S1: Weigh the raw materials according to the weight parts, add unsaturated polyester resin, polystyrene, dicumyl peroxide and wetting and dispersing agent BYK-W996 into a mixer and mix evenly, then add the graphene hybrid flame retardant prepared in Example 2, zinc stearate, calcium carbonate and magnesium oxide and mix evenly to obtain a mixed paste. Step S2: Spread chopped glass fibers evenly on one side of a polypropylene film, then coat the surface of the chopped glass fibers with a mixed paste, then use a pressure roller to fully impregnate the mixed paste and glass fibers, then wind them up with a winding machine, and then transfer them to an oven for curing to obtain graphene-modified high flame-retardant SMC composite material. The curing temperature is 65℃.
[0015] Example 6: A method for preparing a graphene-modified high flame-retardant SMC composite material includes the following steps: 80 parts unsaturated polyester resin, 18 parts polystyrene, 15 parts graphene hybrid flame retardant prepared in Example 3, 4 parts benzoyl peroxide, 3 parts zinc stearate, 55 parts calcium carbonate, 4.5 parts magnesium oxide, 6 parts wetting and dispersing agent BYK-W996, and 75 parts chopped glass fiber. Step S1: Weigh the raw materials according to the weight parts, add unsaturated polyester resin, polystyrene, benzoyl peroxide and wetting and dispersing agent BYK-W996 into a mixer and mix evenly, then add the graphene hybrid flame retardant prepared in Example 3, zinc stearate, calcium carbonate and magnesium oxide and mix evenly to obtain a mixed paste. Step S2: Spread chopped glass fibers evenly on one side of a polypropylene film, then coat the surface of the chopped glass fibers with a mixed paste, then use a pressure roller to fully impregnate the mixed paste and glass fibers, then wind them up with a winding machine, and then transfer them to an oven for curing to obtain graphene-modified high flame-retardant SMC composite material. The curing temperature is 80℃.
[0016] Comparative Example 1: This comparative example is a flame-retardant SMC composite material. The difference between this example and Example 6 is that magnesium hydroxide is used instead of the graphene hybrid flame retardant prepared in Example 3. All other aspects are the same.
[0017] Comparative Example 2: This comparative example is a flame-retardant SMC composite material. The difference between this example and Example 6 is that ammonium polyphosphate is used instead of the graphene hybrid flame retardant prepared in Example 3. All other aspects are the same.
[0018] Comparative Example 3: This comparative example is a flame-retardant SMC composite material. The difference between this example and Example 6 is that graphene oxide is used instead of the graphene hybrid flame retardant prepared in Example 3. All other aspects are the same.
[0019] The performance of the flame-retardant SMC composite materials prepared in Examples 4-6 and Comparative Examples 1-3 was tested: Limiting oxygen index test: according to GB / T 2406.2 2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method" tests the limiting oxygen index; Flame retardancy rating test: in accordance with UL Standard 94 tests vertical combustion performance; Bending strength test: GB / T 1449 The 2005 standard, "Test Method for Bending Properties of Fiber Reinforced Plastics," specifies that the bending strength of fiber reinforced plastics is determined using a universal testing machine at a loading speed of 2 mm / min.
[0020] The test results are shown in Table 1: Table 1: Performance Test Results
[0021] As can be seen from Table 1, the flame-retardant SMC composite material prepared in this invention differs from traditional flame-retardant SMC composite materials in the use of graphene hybrid flame retardants, which have the advantages of requiring less and having higher flame-retardant efficiency.
[0022] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the scope defined by the inventive concept, they should all fall within the protection scope of the present invention.
Claims
1. A graphene-modified high flame-retardant SMC composite material, characterized in that, The raw materials include the following parts by weight: 60-80 parts unsaturated polyester resin, 10-18 parts polystyrene, 8-15 parts graphene hybrid flame retardant, 2-4 parts initiator, 1-3 parts release agent, 45-55 parts calcium carbonate, 2.5-4.5 parts magnesium oxide, 3-6 parts wetting and dispersing agent, and 55-75 parts chopped glass fiber. The graphene hybrid flame retardant is prepared by reacting functionalized graphene with phytic acid. The functionalized graphene is prepared by reacting graphene oxide with a triazine-furan derivative in an oil bath at 60°C for 12 hours. The triazine-furan derivative is prepared by reacting 2,5-furandicarboxylic acid with melamine via an amide reaction. The graphene oxide is prepared by oxidizing graphite powder under the action of concentrated sulfuric acid, sodium nitrate, and potassium permanganate. The graphene hybrid flame retardant is prepared by the following steps: Step A1: Place a beaker containing concentrated sulfuric acid in an ice-water bath, add graphite powder and stir evenly, then add sodium nitrate and stir for 10 minutes, then add potassium permanganate in three portions and stir at room temperature for 12 hours to form a gel, then slowly add deionized water to dilute into a suspension, then add 30wt% hydrogen peroxide and stir for 24 hours, centrifuge, wash until neutral, freeze dry to obtain graphene oxide. Step A2: Under nitrogen atmosphere, add 2,5-furandicarboxylic acid, melamine, DMF and 98wt% concentrated sulfuric acid to a flask in sequence, stir thoroughly, heat to 120-140℃ and reflux for 7-9 hours, add water and shake for 30 minutes, let stand to separate the layers, collect the organic layer, wash the organic layer and dry it under vacuum to obtain the triazine-furan derivative. Step A3: Disperse graphene oxide in water by ultrasonication for 30 min, adjust the pH of the system to 7.5-8.5, add triazine-furan derivative and sonicate while stirring for 15 min, then transfer to an oil bath at 60℃ and stir for 12 h. Centrifuge, wash and dry to obtain functionalized graphene. Step A4: Mix functionalized graphene in water and stir until homogeneous, then add phytic acid and ultrasonically disperse for 30 minutes, then stir at room temperature for 1-2 hours, remove the solvent by rotary evaporation, and vacuum dry to obtain graphene hybrid flame retardant.
2. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, In step A1, the ratio of concentrated sulfuric acid, graphite powder, sodium nitrate, potassium permanganate, deionized water, and hydrogen peroxide is 50mL:2g:0.5-1g:5-7g:300mL:20-30mL.
3. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, In step A2, the ratio of 2,5-furandicarboxylic acid, melamine, DMF, concentrated sulfuric acid, and water is 0.01-0.03 mol: 0.021-0.063 mol: 100 mL: 0.2-0.3 mL: 100 mL.
4. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, The organic layer in step A2 is washed three times with a 0.1 mol / L sodium bicarbonate solution, followed by three washes with water.
5. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, In step A3, the ratio of graphene oxide, water, and triazine-furan derivative is 1g:50mL:0.5-1.5g.
6. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, The pH of the system described in step A3 is adjusted using a 0.5 mol / L sodium hydroxide solution.
7. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, In step A4, the ratio of functionalized graphene, water, and phytic acid is 3g:50mL:2-4g.
8. The graphene-modified high flame-retardant SMC composite material according to claim 1, characterized in that, The initiator is either benzoyl peroxide or dicumyl peroxide, the release agent is zinc stearate, and the wetting and dispersing agent is BYK-W996.
9. A method for preparing a graphene-modified high flame-retardant SMC composite material according to any one of claims 1-8, characterized in that, Includes the following steps: Step S1: Weigh the raw materials according to the weight parts, add unsaturated polyester resin, polystyrene, initiator and wetting and dispersing agent into the mixer and mix evenly, then add graphene hybrid flame retardant, release agent, calcium carbonate and magnesium oxide and mix evenly to obtain the mixed paste. Step S2: Spread chopped glass fibers evenly on one side of a polypropylene film, then coat the surface of the chopped glass fibers with a mixed paste, then use a pressure roller to fully impregnate the mixed paste and glass fibers, then wind them up with a winding machine, and then transfer them to an oven for curing to obtain graphene-modified high flame-retardant SMC composite material. The curing temperature is 50-80℃.
Citation Information
Patent Citations
Graphene-based SMC composite material and preparation method thereof
CN112980210A
Furan diacid-based polyamide resin, preparation method therefor, and polyamide molding composition
WO2023045819A1
